The Effect Of Trap Color On The Population Of Walangsangit Pests In Rice Plants (Oryza sativa L.) - Wahyuni, Siti Hardianti; Siregar, Muhammad Saidi; Parmanoan Harahap (FAKULTAS PERTANIAN UNIVERSITAS RATU SAMBAN, 2025)
This study aims to determine the effect of several types of color traps on the population of stink bugs in rice plantations (Oryza sativa L). This study was conducted from June to October 2023 in the rice fields of Bandar Tarutung Village, Angkola Sangkunur District, South Tapanuli Regency. This research method uses a non-factorial Randomized Block Design (RAK), with treatments consisting of 7 treatments and 3 replications, namely: W₀: Colorless trap, W₁: Yellow trap, W₂: Pink trap, W₃: White trap, W₄: Green trap, W₅: Blue trap, W₆: Red trap. The results showed that the largest population of stink bugs trapped was in treatment W1 (yellow trap), with a total of 31, therefore the best result among all treatments was W1 (yellow trap).